2017
DOI: 10.1177/1076029616686422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Molecular-Weight Heparins Prepared From Bovine Heparins With Enoxaparin

Abstract: Heparin and its low-molecular-weight heparin (LMWH) derivatives are widely used clinical anticoagulants. These drugs are critical for the practice of medicine in applications including kidney dialysis, cardiopulmonary bypass, and in the management of venous thromboembolism. Currently, these drugs are derived from livestock, primarily porcine intestine. The worldwide dependence on a single animal species has made the supply chain for this critical drug quite fragile, leading to the search for other sources of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…$14 g À1 ) and produced on al arge scale for pharmaceutical use.W e envisioned that key IdoA-containing building blocks for HS/ heparin synthesis might be obtained through the controlled hydrolysis of heparin. However,h ydrolysis of heparin under basic conditions results in b-elimination to form unsaturated uronic acid moieties, [5] while nitrous acid mediated depolymerization of heparin is accompanied by deaminative ring contraction of GlcN. [6] Fortunately,elegant studies by Davidson and Meyer, [7] as well as Lopin and Jacquinet, [8] showed that chondroitin sulfate (CS) could be hydrolyzed using aqueous H 2 SO 4 to provide GlcA-N-acetylgalactosamine (GalNAc) disaccharides.S elective cleavage of the GalNAcÀ GlcA bond was presumably facilitated by neighboring group participation from the N-acetyl group of GalNAc.…”
Section: Resultsmentioning
confidence: 99%
“…$14 g À1 ) and produced on al arge scale for pharmaceutical use.W e envisioned that key IdoA-containing building blocks for HS/ heparin synthesis might be obtained through the controlled hydrolysis of heparin. However,h ydrolysis of heparin under basic conditions results in b-elimination to form unsaturated uronic acid moieties, [5] while nitrous acid mediated depolymerization of heparin is accompanied by deaminative ring contraction of GlcN. [6] Fortunately,elegant studies by Davidson and Meyer, [7] as well as Lopin and Jacquinet, [8] showed that chondroitin sulfate (CS) could be hydrolyzed using aqueous H 2 SO 4 to provide GlcA-N-acetylgalactosamine (GalNAc) disaccharides.S elective cleavage of the GalNAcÀ GlcA bond was presumably facilitated by neighboring group participation from the N-acetyl group of GalNAc.…”
Section: Resultsmentioning
confidence: 99%
“…We envisioned that key IdoA‐containing building blocks for HS/heparin synthesis might be obtained through the controlled hydrolysis of heparin. However, hydrolysis of heparin under basic conditions results in β‐elimination to form unsaturated uronic acid moieties, while nitrous acid mediated depolymerization of heparin is accompanied by deaminative ring contraction of GlcN . Fortunately, elegant studies by Davidson and Meyer, as well as Lopin and Jacquinet, showed that chondroitin sulfate (CS) could be hydrolyzed using aqueous H 2 SO 4 to provide GlcA‐ N ‐acetylgalactosamine (GalNAc) disaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…The use of nitrite in the lysis process has caused serious environmental pollution, and the drug activity of prepared LMWHs is low. However, LMWH production still requires the use of chemical degradation instead of purely enzymatic degradation due to the low production and activity of enzymes [35]. Natural HepI is mainly produced by Pedobacter heparinus [36].…”
Section: Discussionmentioning
confidence: 99%